Genetics Insight for COVID-19 Susceptibility and Severity: A Review - Fricke-Galindo, Ingrid; Falfán-Valencia, Ramcés (Frontiers in Immunology, 2021)
Coronavirus disease (COVID-19) presents a broad spectrum of clinical manifestations ranging from an asymptomatic to a severe clinical course. The host genetic background's influence in the susceptibility and outcome of multiples infectious diseases has been previously described. We provide an overview of the complexity of COVID-19 with special attention to the involvement of relevant identified genetic variants and those potentially related to the inter-individual variability of COVID-19 susceptibility and/or severity. The HLA-A*25:01, -B*15:27, -B*46:01, -C*01:02, and -C*07:29 alleles have been associated with COVID-19 susceptibility; while HLA-A*02:02, -B*15:03, and -C*12:03 have been identified as low-risk alleles. Variants in cytokine genes such as IL1B, IL1R1, IL1RN, IL6, IL17A, FCGR2A, and TNF could be related to disease susceptibility and cytokine storm, and/or COVID-19 complications (e.g., venous thrombosis). Several variants in ACE2 and TMPRSS2 affecting the expression of the receptors related to COVID-19 have been associated with the disease susceptibility and risk factors. Finally, two GWAS have identified the loci 3p21.31 (LZTFL1, SLC6A20, CCR9, FYCO1, CXCR6, and XCR1) and 9q34.2 (ABO) with COVID-19 severity. Controversial results in genetic studies of COVID-19 susceptibility and severity have been observed. The mechanism of identified risk-genes and studies in different populations are still warranted.